2011
DOI: 10.1258/shorts.2011.011100
|View full text |Cite
|
Sign up to set email alerts
|

Increased length of inpatient stay and poor clinical coding: audit of patients with diabetes

Abstract: ObjectivesPeople with diabetes stay in hospital for longer than those without diabetes for similar conditions. Clinical coding is poor across all specialties. Inpatients with diabetes often have unrecognized foot problems. We wanted to look at the relationships between these factors.DesignA single day audit, looking at the prevalence of diabetes in all adult inpatients. Also looking at their feet to find out how many were high-risk or had existing problems.SettingA 998-bed university teaching hospital.Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…The evaluation of the adjusted influence of diabetes on length of hospital stay show that patients with diabetes stay on average 1.1 days longer than patients with no diabetes or prediabetes. This significant impact of diabetes on the length of hospital stay is confirmed by other studies [11,20]. A previous study showed that the activation and subsequent intervention of a diabetes care team diminishes the average length of stay of patients with diabetes [20].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The evaluation of the adjusted influence of diabetes on length of hospital stay show that patients with diabetes stay on average 1.1 days longer than patients with no diabetes or prediabetes. This significant impact of diabetes on the length of hospital stay is confirmed by other studies [11,20]. A previous study showed that the activation and subsequent intervention of a diabetes care team diminishes the average length of stay of patients with diabetes [20].…”
Section: Discussionsupporting
confidence: 73%
“…Unknown/undiagnosed diabetes is an additional risk factor for myocardial infarction and mortality, especially in ICU patients [9,10]. Furthermore, diabetic patients do not only have a higher risk of in-hospital mortality when suffering from an acute myocardial infarction [11], but also have a longer hospital stay than those without diabetes [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The retrospective design relies heavily on both the ability of the treating team and the clinical coding team to accurately capture all relevant patient data and assign a correct primary diagnosis [ 26 ]. Errors may also occur in the ICD-10 conversion to the correct DRG [ 28 ]. A prospective study would allow greater accuracy in coding and classification.…”
Section: Discussionmentioning
confidence: 99%
“…Because the data presented in this study were contemporaneously collected by a small number of specialist staff who knew almost all of the patients personally, we were confident that we had a complete data set. However, admissions from other sources collected from clinical coding such as the Accident and Emergency department or Emergency Assessment Units were not recorded in this study because previous work done in our institution has shown inaccuracies in clinical coding and discharge data (10). …”
Section: Methodsmentioning
confidence: 99%